APPLICATION OF MATHEMATICAL MODELS FOR THE SIMULATION OF THERMAL COMFORT CONDITIONS IN A LIVING ROOM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper deals with the distributions of temperature and averaged turbulent airflows in living rooms in 2D and 3D approximations using Ansys/Flotran and Ansys/CFX software respectively. The distributions are calculated depending on the placement and temperature of heaters, heat transfer coefficients of the building structures and ventilation conditions. The authors analyse the influence of these factors on the air circulation and the related heat flows through building structures. The thermal balance of a room and its dependence on various external factors is also considered. As thermal comfort conditions’ parameters are analysed, the airflow velocities and indoor temperatures with its gradients. It is shown that it is possible to save heating consumption, at the same time maintaining the conditions of thermal comfort in the room.